2015
DOI: 10.1177/1753944715572958
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and in vitro and in vivo biological investigation on the antihypertensive activity of mango leaves (Mangifera indica L.)

Abstract: Aims:The aim of this study was to investigate the antihypertensive effect of leaves Mangifera indica L. using in vitro and in vivo assays. Methodology: The ethanol extract of leaves of M. indica was fractionated to dichloromethanic, n-butyl alcohol and aqueous fractions. The chemical composition of ethanolic extract and dichloromethanic fraction were evaluated by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). Antioxidant activity was evaluated in the DPPH scavenging activity assay. Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Hemodynamic and arterial baroreflex assessment of the dichloromethane fraction of mango leaves has been performed, as well. In addition to inhibition of ACE, cardiac hypertrophy in spontaneously hypertensive rats treated with the dichloromethane fraction decreased and the ratio heart weight/body weight increased [166].…”
Section: In Vivo Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Hemodynamic and arterial baroreflex assessment of the dichloromethane fraction of mango leaves has been performed, as well. In addition to inhibition of ACE, cardiac hypertrophy in spontaneously hypertensive rats treated with the dichloromethane fraction decreased and the ratio heart weight/body weight increased [166].…”
Section: In Vivo Studiesmentioning
confidence: 95%
“…The effects of bioactive compounds are generally assessed in vivo studies by the measurement of systolic blood pressure (SBP) of the animal model and analysis of the variation on mean arterial pressure to determine the chronic and acute effect of a compound, respectively [165][166][167][168]. In addition to the combination of bioactive compounds, the definition of the individual compounds' mechanism of action has also been carried out by in vivo studies.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…[ 14 ] In ayurvedic literature, different parts of this plant have been recommended as a remedy for various ailments. It is reported as antidiabetic,[ 15 ] anti-oxidant,[ 16 ] antiviral,[ 17 ] cardiotonic,[ 18 ] hypotensive,[ 19 ] anti-inflammatory,[ 20 ] antibacterial,[ 21 ] antifungal,[ 22 ] anthelmintic,[ 23 ] antiparasitic,[ 24 ] antitumor,[ 25 ] anti-HIV,[ 25 ] anti-bone resorption,[ 26 ] antispasmodic,[ 27 ] antipyretic,[ 27 ] antidiarrheal,[ 28 ] anti-allergic,[ 29 ] immunomodulation,[ 30 ] hypolipidemic,[ 31 ] hepatoprotective,[ 31 ] antimicrobial,[ 32 ] and gastroprotective. [ 33 ] Phytochemical studies on various parts of M. indica L. revealed that it contains phenolic acids, phenolic esters, flavonols, etc., Mangiferin, a natural C-glucoside xanthone,[ 34 ] has been reported from various parts of M. indica and it had been studied for many pharmacological activities such as antidiabetic, rheumatoid arthritis, anti-inflammatory, hypolipidemic, cardiotonic, and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular reflexes are important mechanisms involved in the control of cardiac function and vascular resistance and maintenance of blood pressure levels . In previous work, our group and others demonstrated the importance and influence of the sensitivity of the baroreflex (BRS) and the Bezold–Jarisch reflex (BJR) on the cardiovascular system control .…”
Section: Introductionmentioning
confidence: 93%